Evaluation of structural health monitoring at the Edgardo Rebagliati Martins hospital with a limited number of accelerometers in the city of Lima - Quispe Ccoyllo, Ricardo (2022)
Structural Health Monitoring (SHM) allows assessing the structural damage in observed buildings through different methodologies, which observe changes in the structural behavior immediately after an earthquake. Some methodologies assess the structural damage by observing its global capacity curve obtained through the displacement and acceleration in all stories, calculated using wavelet transform and double integration process. Due to limited resources, some floors are instrumented, and non-instrumented stories response could be estimated by additional procedures, for instance the spline shape function. In this paper, different arrangements of sensors in the Edgardo Rebagliati Martins Hospital (HERM) are evaluated to find the best possible configuration to estimate the global capacity curve and the interstories capacity curves. A 14-story building in the HERM is analyzed, and the optimal arrangement to estimate the capacity curve for each interstory capacity curve was using 7 sensors, and 4 sensors were sufficient to estimate the global capacity curve of this building.